Hemorrhagic Syndrome in Babies - R. F. Tepaev; O. B. Gordeeva; V. V. Botvin'eva; O. K. Botvin'ev (Union of pediatricians of Russia, 2015)
Hemocoagulative disorders comprise one of the relevant paediatric problems. The development of the hemorrhagic syndrome in babies is associated with severe complications, serious health disorders and a decrease in the survival rate. The article covers the issues of etiology, pathogenesis, clinical picture, differential diagnosis and treatment of hemorrhagic syndromes in babies. The authors describe the qualitative and quantitative differences in the in the plasma hemostasis between premature, mature newborns, early age children and adult patients. The study presents main diagnostic methods, which are based on using both routine tests for investigating the plasma hemostasis and second-level (supporting) tests available for the majority of paediatric facilities. The modern approaches to treating hemorrhagic states in early age children are also highlighted. Children with minimal hemorrhagic syndrome manifestations, as well as patients with liver diseases, cholestasis, cystic fibrosis, chronic digestive diseases who have been receiving antibiotic therapy for a long period of time should have an additional homeostasis system survey done in order to timely and correctly diagnose and correct hemorrhagic states. Risk group children are recommended for prophylaxis of vitamin K deficiency. The article is illustrates by 3 clinical observations.